The president's call : executive leadership from FDR to George Bush - Michaels, Judith E., 1948- (Pittsburgh, Pa. : University of Pittsburgh Press, 1997)
Judith Michaels provides an in-depth examination of the Senate-confirmed presidential appointees of the Gorge H. W. Bush administration, and analyzes what these choices reveal about him, his administration, and the institution of political appointments itself. She compares this research to other administrations in the modern era. Particularly fascinating is how Bush's appointees compare with those of Ronald Reagan.
Presidential appointees in the modern era -- Politicization and depoliticization in the nation's pressure cooker -- Appointments and appointees in a politicized atmosphere -- PAS quality and qualifications -- Political-career relations in the modern era -- The Bush Senate-confirmed presidential appointees -- Intrabureaucratic issues : "here, ruining people is considered sport" -- Interbureaucratic issues : the end of village isolation.
Includes bibliographical references (pages 335-341) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Electronic reproduction.
Keywords: USA -- Präsident; United States -- Officials and employees -- Selection and appointment -- History -- 20th century; Government executives -- Selection and appointment -- United States -- History -- 20th century; Presidents -- United States -- History -- 20th century; United States -- Politics and government -- 1933-1945.; United States -- Politics and government -- 1945-1989.; United States -- Politics and government -- 1989-1993.; Hauts fonctionnaires -- Sélection et nomination -- États-Unis -- Histoire -- 20e siècle.; Présidents -- États-Unis -- Histoire -- 20e siècle.; États-Unis -- Politique et gouvernement -- 1933-1945.; États-Unis -- Politique et gouvernement -- 1945-1989.; États-Unis -- Politique et gouvernement -- 1989-1993.; POLITICAL SCIENCE -- Public Affairs & Administration; Government executives -- Selection and appointment; Politics and government; Presidents; United States; Minister; Auswahl; Geschichte 1933-1993.; 1900-1999; Government executives -- Selection and appointment -- United States -- History -- 20th century; Presidents -- United States -- History -- 20th century; United States -- Officials and employees -- Selection and appointment -- History -- 20th century; United States -- Politics and government -- 1933-1945; United States -- Politics and government -- 1945-1989; United States -- Politics and government -- 1989-1993; History